EGFR and COX-2 Dual Inhibitor: The Design, Synthesis, and Biological Evaluation of Novel Chalcones - Arafa Musa; Ehab M. Mostafa; Syed Nasir Abbas Bukhari; Nasser Hadal Alotaibi; Ahmed H. El-Ghorab; Amr Farouk; AbdElAziz A. Nayl; Mohammed M. Ghoneim; Mohamed A. Abdelgawad (Molecules, 2022)
For most researchers, discovering new anticancer drugs to avoid the adverse effects of current ones, to improve therapeutic benefits and to reduce resistance is essential. Because the COX-2 enzyme plays an important role in various types of cancer leading to malignancy enhancement, inhibition of apoptosis, and tumor-cell metastasis, an indispensable objective is to design new scaffolds or drugs that possess combined action or dual effect, such as kinase and COX-2 inhibition. The start compounds A1 to A6 were prepared through the diazo coupling of 3-aminoacetophenone with a corresponding phenol and then condensed with two new chalcone series, C7–18. The newly synthesized compounds were assessed against both COX-2 and epidermal growth factor receptor (EGFR) for their inhibitory effect. All novel compounds were screened for cytotoxicity against five cancer cell lines. Compounds C9 and G10 exhibited potent EGFR inhibition with IC50 values of 0.8 and 1.1 µM, respectively. Additionally, they also displayed great COX-2 inhibition with IC50 values of 1.27 and 1.88 µM, respectively. Furthermore, the target compounds were assessed for their cytotoxicity against pancreatic ductal cancer (Panc-1), lung cancer (H-460), human colon cancer (HT-29), human malignant melanoma (A375) and pancreatic cancer (PaCa-2) cell lines. Interestingly, compounds C10 and G12 exhibited the strongest cytotoxic effect against PaCa-2 with average IC50 values of 0.9 and 0.8 µM, respectively. To understand the possible binding modes of the compounds under investigation with the receptor cites of EGFR and COX-2, a virtual docking study was conducted.